Efficacy and safety of extracorporeal shock wave lithotripsy for chronic pancreatitis. (1st November 2016) - Vaysse, Thibaut; Boytchev, Isabelle; Antoni, Guillemette; Croix, Damien Sainte; Choury, André Daniel; Laurent, Valérie; Pelletier, Gilles; Buffet, Catherine; Bou-Farah, Rita; Carbonnel, Franck
Abstract: Introduction: There is still uncertainty regarding the efficacy and optimal modalities of extracorporeal shock wave lithotripsy (ESWL) in the treatment of chronic pancreatitis. The aims of the present study were to assess the safety and the efficacy of ESWL, either alone or followed by therapeutic endoscopic retrograde cholangiopancreatography (adjuvant ERCP) and to determine predictive factors of efficacy, in a real-life setting. Patients and methods: This study included all consecutive patients who underwent an ESWL in a single University Hospital between 2001 and 2012. The indication for ESWL was obstructive stone(s) of the main pancreatic duct resulting in either painful chronic pancreatitis or recurrent acute pancreatitis. Success was defined by resolution of pain, no analgesic treatment, no acute pancreatitis and no surgical treatment for chronic pancreatitis 6 months after the ESWL. Results: One hundred and forty-six patients were studied; 6/146 (4%) had a complication of ESWL. Among the 132 patients in whom follow-up was completed, 91 (69%) had an adjuvant ERCP. After 6 months of follow-up, 100/132 (76%) patients achieved success. In multivariate analysis, the single significant predictive factor of the success of the ESWL treatment was chronic pain ( p  = 0.03). Patients who had chronic pain and needed opioid treatment had less chance of success than patients without chronic pain (OR 95%CI 0.31 [0.07–1.14]). We found no difference in the success rates between patients who underwent adjuvant ERCP and those who had ESWL only ( p  = 0.93). Conclusion: This study shows that the ESWL is a safe and effective treatment for patients with chronic pancreatitis and obstructive stones within the main pancreatic duct. Systematic association with therapeutic ERCP appears to provide no additional benefit and is therefore not recommended.